Parches juveniles e imaginarios de la violencia en la ciudad de Cali - López-Castillo, Claudia Lorena (Prospectiva. Revista de Trabajo Social e Intervención Social, 2009)
This document presents the most relevant findings of a study conducted with teenagers that make part of a juvenile gang at Conquistadores, a neighborhood in the city of Cali. The objective is to present the imaginaries of these youngsters about the violent actions they commit, as well as the relationships they establish with their environment. In order to accomplish this objective, there will be a description of some violent acts and of the meanings and motivations to perpetrate them. Similarly, this study will explain the influence of familiar dynamics, close surroundings and the context in the reproduction and continuation of violent acts.